APPLICATION OF MARKETING STRATEGIES IN ENTREPRENEURSHIP DEVELOPMENT IN THE UMKM SECTOR - Deddy Hendarwan; Muhammad Giggs Herdarwan; Muhammad Ghazali Herdarwan (Asosiasi Prodi Manajemen Administrasi Pendidikan Indonesia (APMAPI), 2025)
A marketing strategy is a road map that guides a company to achieve its marketing goals. In an entrepreneurial context, where fierce competition and rapid change are the norm, having a solid marketing strategy is key to differentiating a business, attracting potential customers, and achieving sustainability. Market analysis helps identify customer needs, market trends, and exploitable opportunities. In-depth knowledge of competitors enables entrepreneurs to determine their competitive advantage. Successful marketing strategies understand the importance of market segments and targeting. By identifying the market segments most responsive to their products or services, entrepreneurs can craft more tailored and effective messages. Precise targeting helps allocate marketing resources more efficiently. One key to a successful marketing strategy in entrepreneurship is adaptability. Entrepreneurs need to be ready to adapt to changing markets, consumer trends, and technology. Responding quickly to change allows businesses to remain relevant and competitive. Every marketing strategy should be closely linked to business objectives. Whether it is increasing sales, brand awareness, or market share, every step in the marketing strategy should support the achievement of established goals